Corporate Donations as a Source of Financing an Innovative Strategic Economic Plan to Strengthen the National Economy in More Than One Axis in Developing and Poor Countries: A Justified View - Younis A. Battal Saleh (Entrepreneurship Faculty, Universitas Garut, 2021)
In developing and poor countries, corporate donations, which are one of the sources of financing available in those countries, are not being used effectively ″in a correct and ideal way.″ As a result, this theoretical study presented an idea about how to manage and invest this resource in a fruitful way that contributes to strengthening the national economy in more than one axis and addressing many social problems and negative phenomena resulting from the deterioration of economic conditions in those countries, through a strategic economic plan was designed for this purpose. To a large extent, the structure of this study, the formulation of its idea and the formation of its conceptual framework depended on personal diligence, rational thinking and the researcher's imagination, supported by logical justifications. Corporate donations can be used according to the innovative strategic plan to boost the national economy in more than one axis in those countries ″doubling the number of companies - strengthening the infrastructure - enhancing the state's tax revenues - contributing to solving the unemployment problem, etc. ″.Also, this plan will contribute to solving many social problems resulting from the deterioration of the economic conditions in these countries. This is on the practical level, but on the theoretical level, in the field of CSR thought, this study indicated the need to adopt the concept of priority